Infrared Spectroscopy of Hydrated Amino Acids in the Gas Phase: Protonated and Lithiated Valine - Kamariotis, Anthi; Boyarkin, Oleg V; Mercier, Sébastien R; Beck, Rainer D; Bush, Matthew F; Williams, Evan R; Rizzo, Thomas R (Journal of the American Chemical Society, 2006)
We report here infrared spectra of protonated and lithiated valine with varying degrees of hydration in the gas phase and interpret them with the help of DFT calculations at the B3LYP/6-31++G** level. In both the protonated and lithiated species our results clearly indicate that the solvation process is driven first by solvation of the charge site and subsequently by formation of a second solvation shell. The infrared spectra of Val·Li+(H2O)4 and Val·H+(H2O)4 are strikingly similar in the region of the spectrum corresponding to hydrogen-bonded stretches of donor water molecules, suggesting that in both cases similar extended water structures are formed once the charge site is solvated. In the case of the lithiated species, our spectra are consistent with a conformation change of the amino acid backbone from syn to anti accompanied by a change in the lithium binding from a NO coordination to OO coordination configuration upon addition of the third water molecule. This change in the mode of metal ion binding was also observed previously by Williams and Lemoff [J. Am. Soc. Mass Spectrom. 2004, 15, 1014−1024] using blackbody infrared radiative dissociation (BIRD). In contrast to the zwitterion formation inferred from results of the BIRD experiments upon addition of a third water molecule, our spectra, which are a more direct probe of structure, show no evidence for zwitterion formation with the addition of up to four water molecules.